PENGARUH UANG MUKA DAN LAMA ANGSURAN TERHADAP VOLUME PENJUALAN MOTOR YAMAHA PADA CV. CITRA SELARAS RAHA - Hasbudin, H; Hidayah, Waode Nur (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACK Selling strategies policy in this study refers to down payment and the long of payment installation and the effect toward the selling volume of a corporation.consumers are sensitive in these terms. Therefore,the sum down payment and long of installation are alternative strategies can be applied of a corporation to increase the selling volume. The objective of this study wais to know the effect of determining sum of down payment and long of installation toward the selling volume simultaneously and partially of Yamaha motorcycle on CV. Citra Selaras Raha. The data were analyzed by multiple linear regression. Based on the result of analysis showed that the regression equation was Y= 47,963 + 0,627X1 - 0,101X2 and coefficient of determinasi was R2 = 0,937. Based on the result of analysis above, it can be concluded that variable of down payment and long of installation have significant effect toward the selling volume simultaneously and variable of down payment has significant effect toward selling volume partially, while variable of long installation has not significant effect toward selling volume partially.Keyword: Down Payment, Long Of Installation and Selling Volume.